Effectiveness of direct‐acting antiviral therapy among Aboriginal and Torres Strait Islander peoples with HCV infection in Australia: A national real‐world cohort (REACH‐C). Issue 5 (24th January 2023) - Hudson‐Buhagiar, Jessica; Carson, Joanne; Monaghan, Scott; Collie, Patricia; Nelson, Renjy; Van Gessel, Helen; Read, Phillip; Hanson, Josh; Monaghan, Robert; Matthews, Gail; Dore, Gregory J.; Martinello, Marianne; et al.
Abstract: Aboriginal and Torres Strait Islander peoples experience a disproportionate burden of hepatitis C virus (HCV) infection. This study assessed the effectiveness of direct‐acting antiviral (DAA) therapy among Aboriginal peoples in the three years following universal access in Australia. REACH‐C, a national multicentre prospective cohort study, evaluated HCV treatment outcomes from sequential DAA initiations across 33 health services between March 2016 and June 2019. DAA effectiveness was assessed by sustained virological response (SVR) in the total (full analysis set) and effectiveness (modified analysis set excluding those lost to follow‐up) populations. Overall, 915 (10%) Aboriginal and 8095 (90%) non‐Indigenous people commenced DAA therapy, of whom 30% and 16% reported current injecting drug use and 73% and 42% were treated in primary care, respectively. SVR in the total and effectiveness populations was 74% and 94% among Aboriginal people and 82% and 94% among non‐Indigenous people, with loss to follow‐up contributing to lower SVR in the total population analysis (22% Aboriginal, 13% non‐Indigenous). Among Aboriginal people, returning for follow‐up was positively associated with older age (aOR 1.20; 95% CI 1.04, 1.39) and SVR was negatively associated with cirrhosis (aOR 0.39; 95% CI 0.19, 0.80) and prior DAA treatment (aOR 0.14; 95% CI 0.04, 0.49). Factors reflecting higher vulnerability or inequity were not associated with returning for testing or SVR. DAA therapy was highly effective among Aboriginal peoples with HCV treated through primary and tertiary services. Tailored community‐led interventions are necessary to optimize follow‐up and engagement. Sustained DAA uptake and equitable access to care, treatment and prevention are required for HCV elimination.